Evaluating and Improving Online Intelligence Courses - Dr. Alexandra Luce (Journal of Strategic Security, 2013)
Civilian, military and government institutions offer a wide range of courses on intelligence and are increasingly doing so online. While evaluation and improvement are critical to ensuring quality training and education, there is little research about how to evaluate and improve online intelligence courses. Based on the author’s experience developing and teaching such courses, this article offers four suggestions to those involved in online intelligence training and education: (1) conduct a key assumptions check; (2) ensure the course presentation embodies the principles of intelligence communication; (3) encourage creative freedom; and (4) build in mechanisms for feedback throughout the course.